A Proof-of-Concept Evaluation of JTPc and Tp-Tec as Proarrhythmia Biomarkers in Preclinical Species: A Retrospective Analysis by an HESI-Sponsored Consortium. (January 2019) - Boulay, Emmanuel; Abernathy, Matthew M.; Chui, Ray; Friedrichs, Gregory S.; Gendron-Parra, Nicolas; Greiter-Wilke, Andrea; Guillon, Jean-Michel; Koerner, John E.; Menard, Ariane; Steidl-Nichols, Jill; Pierson, Jennifer; Pugsley, Michael K.; et al.
Introduction: Based on the ICH S7B and E14 guidance documents, QT interval (QTc) is used as the primary in vivo biomarker to assess the risk of drug-induced torsades de pointes (TdP). Clinical and nonclinical data suggest that drugs that prolong the corrected QTc with balanced multiple ion channel inhibition (most importantly thel -type calcium, Cav1.2, and persistent or late inward sodium current, Nav1.5, in addition to human Ether-à-go-go-Related Gene [hERG] IKr or Kv11.1) may have limited proarrhythmic liability. The heart rate-corrected J to T-peak (JTpc) measurement in particular may be considered to discriminate selective hERG blockers from multi-ion channel blockers. Methods: Telemetry data from Beagle dogs given dofetilide (0.3 mg/kg), sotalol (32 mg/kg), and verapamil (30 mg/kg) orally and Cynomolgus monkeys given medetomidine (0.4 mg/kg) orally were retrospectively analyzed for effects on QTca, JTpca, and T-peak to T-end covariate adjusted (Tpeca) interval using individual rate correction and super intervals (calculated from 0-6, 6-12, 12-18, and 18-24 hours postdose). Results: Dofetilide and cisapride (IKr or Kv11.1 blockers) were associated with significant increases in QTca and JTpca, while sotalol was associated with significant increases in QTca, JTpca, and Tpeca. Verapamil (a Kv11.1 and Cav1.2 blocker) resulted in a reduction in QTca and JTpca, however, and increased Tpeca. Medetomidine was associated with a reduction in Tpeca and increase in JTpca. Discussion: Results from this limited retrospective electrocardiogram analysis suggest that JTpca and Tpeca may discriminate selective IKr blockers and multichannel blockers and could be considered in the context of an integrated comprehensive proarrhythmic risk assessment.